Digital Access to Healthcare Services and Healthcare Utilization: A Quasi-Experiment - Armenak Antinyan; Stefania Bellio; Marco Bertoni; Luca Corazzini; Elena Narne (Institute of Labor Economics (IZA), 2021)
An Italian region introduced a web portal allowing women to manage online their appointment in the public cervical cancer screening program, besides the standard possibility of doing it via phone. We report quasi-experimental evidence on how access to the portal changes screening behaviour. We find that eligible women do manage their appointment online. The introduction of the portal also reduces attendance of the screening program. Two factors contribute to explain this finding. First, by encouraging women not to take a screening test if they performed an analogous one in the previous three years, the portal reduces overly-frequent screening. Second, the portal induces procrastination in rescheduling the appointment. We also find that, when they cancel their appointment online, women are more likely to share information about their screening episodes in the private health sector, that is useful to schedule future screening appointments.
Keywords: H51; O33; I12; D91; 330; ICT intervention; cervical cancer; screening uptake; quasi-experiment